How Does Telemedicine-Based Postoperative Monitoring Affect Recovery Outcomes and Healthcare Costs for Women Undergoing Gynecological Procedures? : A Systematic Review - Melati Ganeza (The Indonesian Journal of General Medicine, 2026)
Introduction: Postoperative care following gynecological surgery traditionally relies on in-person visits, which impose burdens on patients and healthcare systems. Telemedicine offers a potential alternative, but its impact on recovery outcomes and costs specifically for gynecological procedures requires systematic evaluation. Methods: This systematic review followed structured screening and data extraction procedures. We included randomized controlled trials, etc involving adult women (≥18 years) undergoing routine gynecological procedures. Studies examined telemedicine-based postoperative monitoring (remote technologies, virtual consultations, mobile apps, telehealth platforms) compared to standard care. Outcomes included recovery measures (complications, readmissions, patient satisfaction, quality of life, return to activities) and healthcare costs. Sixteen studies met inclusion criteria for final analysis. Results: Patient satisfaction was noninferior or superior to standard care across 10 studies (Lee et al., 2020; Wherley et al., 2025; Robin et al., 2025). Functional recovery improved significantly with comprehensive eHealth programs combining activity tracking and personalized advice, reducing return-to-normal-activities by 13 days (den Bakker et al., 2023). Simple telephone follow-up showed no benefit on quality of life or pain in enhanced recovery settings (Kassymova et al., 2020; Kassymova et al., 2022). Telemedicine was safe across all studies, with no increased complications or readmissions. Cost-effectiveness was demonstrated for internet-based programs (Bouwsma et al., 2018) and automated low-cost interventions (Sajnani et al., 2020; Robin et al., 2025), while nurse-led telephone models doubled costs without clinical benefit (Kassymova et al., 2025). Discussion: Intervention complexity predicts functional recovery benefits; personalized, interactive eHealth platforms outperform passive monitoring. Enhanced recovery after surgery (ERAS) contexts may attenuate marginal benefits of simple telephone follow-up. Satisfaction is universally preserved across all telemedicine modalities. Telemedicine does not increase low-acuity healthcare contacts and may reduce them through structured coaching. Cost-effectiveness depends on mechanism of savings—technology-mediated scalable interventions are superior to staffing-intensive models. Patient age, technological literacy, and psychological factors influence uptake and outcomes. Conclusion: Telemedicine-based postoperative monitoring for gynecological procedures is safe and achieves patient satisfaction equivalent or superior to standard care. Functional recovery benefits require comprehensive, personalized interventions with active patient engagement rather than simple follow-up. Cost-effectiveness favors automated or internet-based programs over labor-intensive telephone models. Future implementation should match intervention complexity to clinical context, target specific care gaps (activity guidance, expectation management), and consider patient digital literacy and psychological needs.